Is backsliding possible on Xunzi’s view? - Sung, Winnie (2024)
This study raises the question whether it is possible, in Xunzi’s 荀子 view, for someone who has gone through moral transformation to backslide. I consider three possible interpretations. On the first interpretation, one’s dispositions are transformed by environmental forces. Backsliding is possible and likely. I rule out this interpretation because it is inconsistent with other aspects of Xunzi’s thought. On the second interpretation, one’s kind-determining constitution is transformed from a neutral constitution to a moral constitution. Backsliding is not possible because one has acquired a moral constitution that is insusceptible to bad environmental influences. On the third interpretation, to be transformed is to have accumulated significantly more moral knowledge than ordinary untransformed people. Backsliding is possible but unlikely. I will then explain why it is difficult to adjudicate between the second and third interpretations and suggest further issues in Xunzi’s thought that need to be investigated.